Untangling cryptic diversity in the High Andes: Revision of the Scytalopus [magellanicus] complex (Rhinocryptidae) in Peru reveals three new species. (21st February 2020) - Krabbe, Niels K; Schulenberg, Thomas S; Hosner, Peter A; Rosenberg, Kenneth V; Davis, Tristan J; Rosenberg, Gary H; Lane, Daniel F; Andersen, Michael J; Robbins, Mark B; Cadena, Carlos Daniel; Valqui, Thomas; Salter, Jessie F; et al.
Abstract: Tropical mountains feature marked species turnover along elevational gradients and across complex topography, resulting in great concentrations of avian biodiversity. In these landscapes, particularly among morphologically conserved and difficult to observe avian groups, species limits still require clarification. One such lineage is Scytalopus tapaculos, which are among the morphologically most conserved birds. Attention to their distinctive vocal repertoires and phylogenetic relationships has resulted in a proliferation of newly identified species, many of which are restricted range endemics. Here, we present a revised taxonomy and identify species limits among high-elevation populations of Scytalopus tapaculos inhabiting the Peruvian Andes. We employ an integrated framework using a combination of vocal information, mitochondrial DNA sequences, and appearance, gathered from our own fieldwork over the past 40 yr and supplemented with community-shared birdsong archives and museum specimens. We describe 3 new species endemic to Peru. Within all 3 of these species there is genetic differentiation, which in 2 species is mirrored by subtle geographic plumage and vocal variation. In a fourth species, Scytalopus schulenbergi, we document deep genetic divergence and plumage differences despite overall vocal similarity. We further propose that an extralimital taxon, Scytalopus opacus androstictus, be elevated to species rank, based on a diagnostic vocal character. Our results demonstrate that basic exploration and descriptive work using diverse data sources continues to identify new species of birds, particularly in tropical environs. Graphical Abstract: